peri -Acenoacenes - Gu, Yanwei; Tullimilli, Y. Gopalakrishna; Feng, Jiaqi; Phan, Hoa; Zeng, Wangdong; Wu, Jishan (Chemical communications (Cambridge, England), 2019)
We report the challenging synthesis and electronic properties of a new class of rhombic peri -fused acene dimers, the so-called peri -acenoacenes. Compared to rectangular peri -fused peri -acenes, peri -acenoacenes show less diradical character and higher stability. Two soluble and stable aryl-substituted peri -acenoacenes, peri -tetracenotetracene ( TT-Ar ) and peri -pentacenopentacene ( PP-Ar ), are synthesized and their structures are confirmed by X-ray crystallographic analysis. Their optical properties and electronic properties are different from those of peri -acene derivatives. Unexpectedly, both the neutral compounds and dications are aromatic.